Parametric Study of Modified U-shaped Split Ring Resonator Structure Dimension at Ultra-Wide-band Monopole Antenna - Ibrahim, I. M.; Al-Gburi, Ahmed Jamal Abdullah; Zakaria, Z.; Bakar, H. A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper discusses the parametric study work Ushaped split ring resonator (SRR) structure effect on the ultrawide-band (UWB) monopole. Five different stages are done, consisted from Design A to Design E, with three stages are considered with parametric study – Design B, Design C, and Design D. Firstly, Design A represent the basic UWB monopole antenna without SRR structure while the last design, Design E shows the proposed UWB monopole antenna with modified SRR structure. The Design E successfully resonate at first resonant frequency of 6.272 GHz with return loss performance of – 25.91 dB while resonate at second resonant frequency at 7.82 GHz with a return loss of – 26.165 dB. This antenna operates at UWB range frequency from 2.572 GHz to 10.746 GHz of with bandwidth performance of 8.174 GHz. It shows that a 0.972 GHz range of band-notch frequency bandwidth, starting with 5.028 GHz to 6.0 GHz.